История Удмуртии в географических названиях: [исследования по топонимике] / М. Г. Атаманов - Атаманов Михаил Гаврилович (Удмуртия, 1997)
Экземпляры: краеведение (20230531) / Инвентарный номер: 29909 / Цена: / Сис.шифр: 63.52(2) / Авт.знак: А 92 / ББК: 63.3(2)Удм.